2020
DOI: 10.1016/j.bja.2020.08.050
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related organ dysfunction and management strategies on the intensive care unit: a narrative review

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has resulted in a significant surge of critically ill patients and an unprecedented demand on intensive care services. The rapidly evolving understanding of pathogenesis, limited disease specific evidence, and demand-resource imbalances have posed significant challenges for intensive care clinicians. COVID-19 is a complex multisystem inflammatory vasculopathy with a significant mortality implication for those admitted to intensive care. Institutional strategic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 121 publications
0
30
0
Order By: Relevance
“… 18 , 19 sHLH and COVID-19 critical illness can manifest similarly, possibly exacerbating the risk of propofol-related hypertriglyceridemia. 33 A recent cross-sectional study demonstrated that high triglyceride concentrations were strong predictors of a severe course of COVID-19. 34 The pathophysiology involves the overexpression of cytokines, and the inflammatory state produced during COVID-19 infection leads to significant changes in lipid metabolism, specifically affecting the lipoprotein lipase enzyme.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 sHLH and COVID-19 critical illness can manifest similarly, possibly exacerbating the risk of propofol-related hypertriglyceridemia. 33 A recent cross-sectional study demonstrated that high triglyceride concentrations were strong predictors of a severe course of COVID-19. 34 The pathophysiology involves the overexpression of cytokines, and the inflammatory state produced during COVID-19 infection leads to significant changes in lipid metabolism, specifically affecting the lipoprotein lipase enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ADAMTS13, the von Willebrand factor-specific protease, seems to be slightly decreased, with a subsequent imbalance of von Willebrand factor/ADAMTS13 axis when considering the strikingly elevated von Willebrand factor levels (Blasi et al, 2020;Delrue et al, 2020;Huisman et al, 2020). Hypoxemia associated with COVID-19-related pneumonia (Sherren et al, 2020) may also enhance hypercoagulability through increased synthesis of hypoxia inducible factor-1α (Marchetti, 2020), which increases procoagulant gene expression (Gupta et al, 2019).…”
Section: Hypercoagulability Favoring Thrombosis In Covid-19 Patientsmentioning
confidence: 99%
“…Moreover, microvascular thrombosis promoting kidney injury and lung microvascular thrombosis promoting hypoxemia (Sherren et al, 2020;Vinayagam and Sattu, 2020) may further increase predisposition to thrombosis.…”
Section: Endothelial Activation and Lesion Favoring Thrombosis In Covmentioning
confidence: 99%
“…Moreover, the severity of organ damage is directly correlated with ACE2 density [55] , [56] . Therefore, most deaths in SARS-CoV-2 infection could be attributed to densely infected lungs [57] . Furthermore, although no association between the central nervous system (CNS) involvement and COVID-19 has been reported, low levels of SARS-CoV-2 have been detected in the brains of patients who died due to COVID-19 [58] .…”
Section: Introductionmentioning
confidence: 99%